Against deep conventionalism. Issue 3 (2nd September 2018) - Moore, Eric
ABSTRACT: William Morgan presents two diametrically opposed normative conceptions of sport and athletic excellence from late nineteenth/early twentieth-century British and American athletes. He claims that this example shows that the normative theory of sport presented by broad internalism (interpretivism) is false or at least inadequate. As an alternative, he presents the concept of deep conventions, which, he claims, can successfully adjudicate such normative disputes. I argue that Morgan's counterexample is not nearly so decisive against broad internalism as it might seem and that his own solution, deep conventionalism (a) does no better in solving the dispute and (b) suffers from further issues of its own.